Carbon dynamics on agricultural land reverting to woody land in Ontario, Canada. (15th May 2017) - Voicu, Mihai F.; Shaw, Cindy; Kurz, Werner A.; Huffman, Ted; Liu, Jiangui; Fellows, Max
Abstract: The 2015 Paris Agreement reinforces the importance of the land sector and its contribution to greenhouse gas (GHG) reductions. Thus, there is growing interest in improving estimates of the GHG balance in response to land-use changes (LUCs) involving agriculture and forestry, for national-scale reporting, and for carbon (C) offsets. Large agricultural areas in Europe, Russia and North America are reverting to forest, either naturally or through planting, after abandonment of agricultural land, and this trend may have a substantial impact on carbon budgets. We report results of a pilot project in the Mixedwood Plains ecozone of eastern Canada to analyze the change in the C budget on a landscape over 15 years on abandoned cropland where woody vegetation is regenerating. Thirty-six plots (2 km × 2 km) with paired aerial photographs taken circa 1994 and circa 2008 at a scale of 1:10, 000 or larger were randomly selected from the 20 km × 20 km National Forest Inventory (NFI) grid. A spatially-explicit version of the Carbon Budget Model of the Canadian Forest Sector (CBM-CFS3) was used to estimate impacts of LUC on C stocks and fluxes. Polygons identifying areas of LUC within each photo plot were delineated, classified, and evaluated to provide input data for the model. The rate of C accumulation in our study area was found to be relatively constant over the entire simulation period, at 1.07 Mg C/ha/yr. Abandoned agricultural land reverting to woody lands could play an important role in regional and national C sequestration in Canada, but more research is required to quantify the areal extent of this LUC. Highlights: Landscape-scale C dynamics were assessed for abandoned agricultural land reverting to forests. The carbon sink was estimated at ∼1 Mg C/ha/yr. The sink strength on a per ha basis was higher than in the managed forest area. Better estimates of the total affected land area are needed for national-scale assessments.